The Art of Re-Interpreting Self: Self Imagery in the Works of Indian Artists - Nazima Rangwala Kalita (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2019)
This study is combining, connecting, or involving many different kinds of artistic disciplines, re-interpreting the event of a self as a new sense of autonomy, and a more modern understanding of individuation. This study aims to examine the knowledge of self-imagery in Indian art through various media and representational techniques of Indian artists' works. Here I will talk about Indian art scenarios in different spaces and times and how Indian artists are affected and how ideas about Self image emerge. The data used in this study are literature data, video of artists' performances, and data on artworks. All data is observed, and the results are separated based on data trends. Separation of information is done by arranging three main variables, namely the background of the life of the artist, the journey of the creation of the work, and the achievements of the artist's work. Observation steps targeting three artists and their actions in India, such as Bhupen Khakhar, Sonia Khurana, and Ranbir Kaleka, further analyzed by referring to the framework of